PERKEMBANGAN PSIKOLOGI ANAK DALAMPENDIDIKAN ISLAM - Abu Bakar (Sosial Budaya, 2011)
Islamic education psychology constitutes a sitem's Sub of psychology knowledge branch that is engaged process learning. Islamic education psychology actually constitute psychology study to day-to-day problem in Islamic education, one that develops principle, models, theory, procedure in learning and works through another issue issue that regard student interaction by learns through al Qur' an and Hadis Rasulullah